2002
DOI: 10.1164/ajrccm.165.2.2108087
|View full text |Cite
|
Sign up to set email alerts
|

Low Tidal Volume Reduces Epithelial and Endothelial Injury in Acid-injured Rat Lungs

Abstract: Using a rat model of acid-induced lung injury, we tested the hypothesis that tidal volume reduction at the same level of PEEP (10 cm H 2 O) would diminish the degree of pulmonary edema by attenuating injury to the alveolar epithelial and endothelial barriers. Tidal volume reduction from 12 to 6 to 3 ml/kg significantly reduced the rate of lung water accumulation from 690 l/h to 310 l/h to 210 l/h. Ventilation with either 6 or 3 ml/kg reduced endothelial injury equally as measured by plasma vWf:Ag and permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
185
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(202 citation statements)
references
References 36 publications
(40 reference statements)
10
185
2
5
Order By: Relevance
“…In Fig. 4, the data obtained from Frank et al 3 relating fluid clearance to decreasing V T can also be shown to fit a convex curvilinear relationship such that Jensen's inequality may also be applied. Using the same low V T protocol, it follows that a variable ventilation strategy may confer benefit with respect to recruitment from the larger breaths and fluid clearance from the smaller breaths invoking the same principle (Jensen's inequality) applied to two separate curvilinear functions: i) disproportionate lung recruitment with improved compliance and gas exchange resulting from the intermittent higher tidal volumes as applied to the convex curvilinear pressure-volume curve and ii) disproportionately greater fluid clearance resulting from the intermittent lower tidal volumes applied to the convex curvilinear fluid clearance-tidal volume curve.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In Fig. 4, the data obtained from Frank et al 3 relating fluid clearance to decreasing V T can also be shown to fit a convex curvilinear relationship such that Jensen's inequality may also be applied. Using the same low V T protocol, it follows that a variable ventilation strategy may confer benefit with respect to recruitment from the larger breaths and fluid clearance from the smaller breaths invoking the same principle (Jensen's inequality) applied to two separate curvilinear functions: i) disproportionate lung recruitment with improved compliance and gas exchange resulting from the intermittent higher tidal volumes as applied to the convex curvilinear pressure-volume curve and ii) disproportionately greater fluid clearance resulting from the intermittent lower tidal volumes applied to the convex curvilinear fluid clearance-tidal volume curve.…”
Section: Discussionmentioning
confidence: 90%
“…Frank et al 3 showed that V T reduction to levels even below that recommended by the ARDSNet trial was associated with the greatest improvement in fluid clearance. Biologically variable ventilation is unique in that both lower (presumably advantageous) and higher (presumably disadvantageous) V T breaths are included in the modulation file.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a rat model of lung injury, Frank et al examined the effect of three different tidal volumes (3, 6 and 12 ml/kg) on lung injury in rats. Their investigation showed that alveolar epithelial injury was a critical part of the pathology because there were elevated plasma levels of rat type I cell 40 kD protein, a marker of type I epithelial cell injury and impaired alveolar fluid clearance, effects that were reduced by lower tidal volume ventilation [39].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
“…Using a rat model of lung injury, Frank et al examined the effect of three different tidal volumes (3, 6 and 12 ml/kg) on lung injury in rats. Their investigation showed that alveolar epithelial injury was a critical part of the pathology because there were elevated plasma levels of rat type I cell 40 kD protein, a marker of type I epithelial cell injury and impaired alveolar fluid clearance, effects that were reduced by lower tidal volume ventilation [39].Radiographically, ALI/ARDS is a heterogeneous process, with areas of normal lung adjacent to fluid-filled alveoli [4]. Thus, normal alveolar units may be subject to much higher local distending pressures when ventilated with a given tidal volume.…”
mentioning
confidence: 99%